A simplified mechanically based model for predicting partially drained behaviour of penetrometers and shallow foundations - Houlsby, G; Cassidy, M (2011)
An analytical model is described for the behaviour of shallow foundations subjected to partially drained vertical penetration. The model is based on a simplified mechanical approach, allowing the calibration of model parameters for different foundation shape, size and soil conditions. As shown through simple examples, the resulting model exhibits (with some limitations) behaviour that closely resembles that obtained from geotechnical centrifuge experiments of a T-bar penetrometer and a circular spudcan footing installed at a variety of rates. An extension of the model to combined vertical and horizontal loading is also possible, although this would require further calibration with experimental data. The model retains a simplicity that may find application in the coupled analysis of offshore structures with foundations that are subjected to loading under different rates and drainage.